PARARENTS’ CONSIDERATIONS FACTORS IN CHOOSING ELEMENTARY SCHOOL - Rizki, Muhammad; Hadi, Sutarto; Sulaiman (Journal of K6, Education and Management, 2019)
Parents always want the best for their children based on their abilities, including education. For this reason, the concept of assimilation in accordance with the wishes of parents is very useful for schools in mapping prospective applicants. The purpose of this study is to identify: a) what factors that considered by students? parents in choosing schools and b) which factors are the most dominant for making decisions in determining schools. This research is a descriptive qualitative research with a multi-site design. Data in this study were collected through observation, in-depth interviews, and documentation. The collected data is then analyzed with an interactive data analysis model consisting of three stages, which are: data reduction, data display, and verification or drawing conclusions. The results of this study indicate that a) the mix factors that are considered by parents in choosing a school are: product, price, location, human resources, and process; and b) the dominant factor being considered by parents in choosing schools, which are products, processes, prices, human resources and location, as well as the foundation of the school's religious philosophy and long-standing positive image. This study recommends that schools that want to increase the number of students should make an increase in the dominant factors into consideration for parents in choosing schools for their children.